2018
DOI: 10.4236/psych.2018.95064
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Researches Workplace Loneliness

Abstract: Workplace health psychology is supported and upheld by psychologists, management scientists, sociologists and clinical psychology. Workplace loneliness has become a hot research topic in western occupational health psychology. The research about the spread of employee workplace loneliness in China is lagging behind. As a common negative emotion in workplace, workplace loneliness can bring in a series of negative effects on employees and individuals. At present in China, the transformation of the society and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 20 publications
0
26
0
14
Order By: Relevance
“…Many factors are effective in experiencing loneliness in the workplace. Personality characteristics of employees, working values, quality of work, working hours, workload, attitudes and behaviors of managers, organizational support, organizational culture, organizational climate, human resources policies are major factors [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Loneliness In the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…Many factors are effective in experiencing loneliness in the workplace. Personality characteristics of employees, working values, quality of work, working hours, workload, attitudes and behaviors of managers, organizational support, organizational culture, organizational climate, human resources policies are major factors [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Loneliness In the Workplacementioning
confidence: 99%
“…On the other hand, loneliness in the workplace can lead to increases in the intention of employees to quit [3][4][5][6][7][8][9][10][11][12][13][14][15][16], organizational cynicism [14] and organization alienation [17]. In addition, loneliness in the workplace can cause stress in employees [18] and impaired health [12]. Negative effects of loneliness in the workplace affect also the success of the organization and peace in the workplace [19].…”
Section: Loneliness In the Workplacementioning
confidence: 99%
“…Wright (2005) states that the perception of loneliness occurs in business life as a result of the effects of individual, organizational and environmental factors on individuals. In the literature, there are many studies examining the relationship between personality traits and loneliness in business life (Levin and Stokes, 1986;Bell et al, 1990;Cheng and Furnham, 2002;Özçelik and Barsade, 2011;Zhou, 2018). When the findings of these researches were examined, it was found that the significant effect of personality traits on loneliness in business life was an important issue to be investigated and contributed to the establishment of the research model.…”
Section: Extended Abstractmentioning
confidence: 99%
“…Wright (2005), bireysel, örgütsel ve çevresel faktörlerin, kişiler üzerindeki etkisi sonucunda iş yaşamında yalnızlık algısının oluştuğunu belirtmektedir. Yazında, kişilik özellikleri ile iş yaşamında yalnızlık arasındaki ilişkiyi inceleyen birçok araştırma bulunmaktadır (Levin ve Stokes, 1986;Bell vd., 1990;Cheng ve Furnham, 2002;Özçelik ve Barsade, 2011;Zhou, 2018). Bu araştırmaların bulguları incelendiğinde, ki-şilik özelliklerinin iş yaşamında yalnızlık üzerinde anlamlı etkisinin, incelenmesi gereken önemli bir konu olduğu tespit edilmiş ve araştırma modelinin kurulmasına katkı sağlamıştır.…”
Section: Introductionunclassified
“…This negative impact on employees' performance is associated with factors such as increased intention to quit, low job satisfaction, weakened organizational commitment, workplace stress, and alienation (Achor et al, 2018;Ayazlar & Guzel, 2014;Çetin & Alacalar, 2016;Ertürk, & Erdirençelebi, 2018;Lam & Lau, 2012;Ozcelik & Barsade, 2018;Wright, 2005). Its negative impact on organizational performance is that it affects other employees in the team and creates a risk factor for organizational success (Stallard, 2019;Zhou, 2018).…”
mentioning
confidence: 99%